PROFITABILITAS, PERTUMBUHAN PERUSAHAAN DAN UKURAN PERUSAHAAN SEBAGAI DETERMINAN STRUKTUR MODAL - Wayan Wardita; Made Purba Astakoni (KRISNA: Kumpulan Riset Akuntansi, 2018)
The purpose of this research is; analyze and explain the effect of profitability on the capital structure, analyze and explain the effect of growth rate (growth) on capital structure, analyze and explain the effect of profitability to the wide company at PT. Mustika Ratu and Subsidiaries. In this research data analysis technique using Partial Least Square (PLS) approach. PLS is a model of Structural Equation Modeling (SEM) equations based on components or variants. Based on hypothesis testing found that profitability have a significant negative effect on capital structure at PT. Mustika Ratu and Subsidiaries. This is indicated by the value of coefficient of -0.20860009 with the value of t-statistics of 14.465286 above the critical value of 1.96, so it shows that the higher the profitability of a company will lower the value of the company's capital structure. Growth rate (growth) has a significant negative effect on capital structure at PT. Mustika Ratu and Subsidiaries. This shows that the higher the company's growth will decrease the value of the company's capital structure. This is indicated by the coefficient value of -0.300925 with a t-statistic value of 20.32658 above the critical value of 1.96, so this indicates that the higher growth rate (a company) will lower the value of the company's capital structure, and firm size (size) have a significant positive effect on capital structure at PT. Mustika Ratu and Subsidiaries. This shows that the higher the size (size) of a company will increase the company's capital structure. This condition is shown by the coefficient value of 0.660465 with the value of t-statistics of 29.89193 (larger 1.96). Keywords: Capital Structure. Profitability, Corporate Growth, Company Size